What is the solution of the system? use substitution . 4x+2y=10, y=-3x+6
3 answers
@steve can you help??
It tells you to use substitution and you already have y, all alone on the left. It is (-3x+6)
so
use that. substitute it for x i the other (first) equation
4 x + 2(-3x+6) = 10
4 x - 6 x + 12 = 10
2 x = 2
x = 1
y = -3(1) + 6 = 3
so
use that. substitute it for x i the other (first) equation
4 x + 2(-3x+6) = 10
4 x - 6 x + 12 = 10
2 x = 2
x = 1
y = -3(1) + 6 = 3
My answer chosies are
a. (1,-3)
b.(1,3)
c.(3/10, 4/5)
d.(-2,-2)
Is it b? @damon
a. (1,-3)
b.(1,3)
c.(3/10, 4/5)
d.(-2,-2)
Is it b? @damon